2004
DOI: 10.1614/wt-03-149r1
|View full text |Cite
|
Sign up to set email alerts
|

Relative Tolerance of Four Cool-Season Turfgrass Species to Sulfosulfuron

Abstract: Field experiments were conducted at Adelphia, NJ, in 2001 and 2002 to evaluate the response of Kentucky bluegrass, perennial ryegrass, tall fescue, and Chewings fine fescue to sulfosulfuron. Single applications of sulfosulfuron at 6 to 67 g ai/ha were applied to mature swards of each species. Visual chlorosis ratings were taken and clippings were collected 4 wk after treatment (WAT), and turf injury was rated 8 WAT. Chlorosis on all species increased with increasing sulfosulfuron rate. In 2001, Kentucky bluegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…Kentucky bluegrass quality remained above acceptable levels throughout the duration of each experiment (data not shown), and quality ratings of Kentucky bluegrass were similar in treated plots like in the untreated plots (P $ 0.2235). These results agree with Lycan and Hart (2004) who demonstrated that Kentucky bluegrass was tolerant to sulfosulfuron and exhibited only temporary discolorations at application rates 0.034 kgÁha -1 or less.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Kentucky bluegrass quality remained above acceptable levels throughout the duration of each experiment (data not shown), and quality ratings of Kentucky bluegrass were similar in treated plots like in the untreated plots (P $ 0.2235). These results agree with Lycan and Hart (2004) who demonstrated that Kentucky bluegrass was tolerant to sulfosulfuron and exhibited only temporary discolorations at application rates 0.034 kgÁha -1 or less.…”
Section: Resultssupporting
confidence: 92%
“…Recent studies demonstrate that sulfosulfuron exhibits herbicidal activity on annual bluegrass (Poa annua L.) (Lycan and Hart, 2002;Taylor et al, 2002) and tall fescue (Festuca arundinacea Schreb.) (Lycan and Hart, 2004), but Kentucky bluegrass and perennial ryegrass (Lolium perenne L.) are tolerant of the herbicide at low application rates (Lycan and Hart, 2004). Although these reports reveal the differential responses of cool-season grasses to sulfosulfuron, its activity on creeping bentgrass is not understood at this time.…”
mentioning
confidence: 99%
“…Other field research demonstrated that four spring applications of sulfosulfuron at 11 g/ha reduced roughstalk bluegrass cover by 74% nine weeks after initial application (10). Kentucky bluegrass and perennial ryegrass have demonstrated adequate tolerance to single applications of sulfosulfuron at 6 to 34 g/ha in field trials (8). Creeping bentgrass appears to be less tolerant to applications of sulfosulfuron than Kentucky bluegrass, and thus multiple applications of sulfosulfuron have the potential to selectively reduce populations of creeping bentgrass within Kentucky bluegrass stands (5).…”
Section: Introductionmentioning
confidence: 99%
“…These five herbicides are safe on bermudagrass and zoysiagrass, with minor safety on other warm-season turfgrasses and these herbicides are active on almost all cool-season turfgrasses (Stephenson IV et al, 2006;Brecke et al, 2008). Sulfosulfuron is the least active on cool-season turfgrasses and has potential use for weed control in cool-season turfgrass (Lycan & Hart, 2004). Thus, these herbicides are commonly utilized in warmseason turfgrass for Poa annua control, with the least effective two being flazasulfuron and sulfosulfuron (Harrell et al, 2005;Toler et al, 2005).…”
Section: Als-inhibiting Herbicidesmentioning
confidence: 99%